Strategies to promote generative reflection in practicum tutorials in teacher training: The representations of tutors and practicum students. Issue 1 (2nd January 2022) - Ruffinelli, Andrea; Álvarez Valdés, Carolina; Salas Aguayo, Macarena
ABSTRACT: This paper investigates the social representations (SR) of tutors and preservice teachers regarding pedagogical strategies that promote generative reflection in practicum tutorials during initial teacher training. Using a qualitative approach, individual and group interviews were conducted with tutors and preservice teachers on video recordings of classes given by the preservice teachers and tutorial sessions. The analysis was inspired by Grounded Theory. The findings reveal that the tutors favour constructivist strategies, but guided strategies are predominant in their training practices, based on their role as experts, which is consistent with the demands of preservice teachers regarding this role. These results conflict with the literature in the area, which points to constructivist strategies as promoting reflective generative practice.